Implementasi Pembelajaran Akidah Akhlak - Indrawan Indrawan; Nur Alim (Edudeena : Journal of Islamic Religious Education, 2022)
Abstrack: This study aims to describe the implementation of aqidah moral learning and find out the supporting and inhibiting factors that arise in the implementation of akidah moral learning in the city of Kendari. The type of research used is a qualitative case study. Data collection carried out is observation, interviews and documentation. The results of the study show that the implementation of akidah akhlak learning refers to the 2013 curriculum. The process of implementing akidah akhlak learning includes preliminary activities, core activities, and closing activities. In preparatory activities, the teacher prepares students mentally and physically and provides motivation and awareness by explaining the importance of the material, learning objectives, and learning procedures. The core activities include the process of exploration, refinement (elaboration), and confirmation. In closing activities the teacher and students together conclude the subject matter, and give assignments to students. The learning method applied is the lecture, question and answer, discussion and assignment methods which are adapted to the methods contained in the teacher's lesson plan and adapted to the material being taught, as well as carrying out learning evaluations in the form of daily tests. Factors that support the implementation of learning Aqidah Akhlak are teachers mastering the material and understanding student personalities to facilitate the learning process. Apart from that, it is also supported by the existence of dormitories so that all students are more controlled because all students are in dormitories and coupled with Islamic boarding school activities. The inhibiting factors are inadequate facilities and inadequate learning resources plus students are prohibited from bringing cellphones as well as students themselves who have family and educational backgrounds so that discipline is needed so that students can understand what is conveyed. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan implementasi pembelajaran akidah akhlak dan mengetahui faktor-faktor pendukung serta penghambat yang muncul dalam implementasi pembelajaran akidah akhlak di kota Kendari. Jenis penelitian yang digunakan adalah studi kasus kualitatif. Pengumpulan data yang dilakukan adalah observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa dalam implementasi pembelajaran akidah akhlak mengacu pada kurikulum 2013. Proses implementasi pembelajaran akidah akhlak meliputi kegiatan pendahuluan, kegiatan inti, dan kegiatan penutup. Dalam kegiatan persiapan, guru mempersiapkan siswa secara mental dan fisik serta memberikan motivasi dan kesadaran dengan menjelaskan pentingnya materi, tujuan pembelajaran, dan prosedur pembelajaran. Kegiatan inti meliputi proses eksplorasi, penyempurnaan (elaborasi), dan konfirmasi. Pada kegiatan penutup guru dan siswa bersama-sama menyimpulkan materi pelajaran, dan memberikan tugas kepada siswa. Metode pembelajaran yang diterapkan yaitu metode ceramah, tanya jawab, diskusi dan penugasan yang disesuaikan dengan metode yang ada dalam RPP guru dan disesuaikan dengan materi yang diajarkan, serta terlaksananya evaluasi pembelajaran dalam bentuk ulangan harian. Faktor yang mendukung terselenggaranya pembelajaran akidah akhlak adalah guru menguasai materi dan memahami kepribadian siswa untuk memudahkan proses pembelajaran. Selain itu, juga didukung dengan adanya asrama sehingga seluruh siswa lebih terkontrol karena seluruh siswa di asramakan dan ditambah dengan adanya kegiatan-kegiatan pondok pesantren. Adapun faktor penghambatnya adalah fasilitas yang kurang memadai, dan sumber belajar yang belum memadai ditambah para siswa dilarang membawa handphone serta siswa sendiri yang mempunyai latar belakang keluarga dan pendidikan yang sehingga kete;adanan sangat diperlukan agar siswa dapat memahami apa yang disampaikan.